THE ROLE OF CIVIC EDUCATION ON DEVELOPING CHARACTER OF RESPONSIBILITY STUDENTS IN THE ERA OF GLOBALIZATION AT SENIOR HIGH SCHOOL 1 BALEENDAH - Aim Abdulkarim, Dinar Sugiana, Sapriya (Jurnal Civicus, 2014)
Civics lesson plan is done by entering the value of character and integrate the syllabus and lesson plans is one of the requirements before making the learning process. Character responsibility integrated into the three stages of learning (1) introduction (2) core activities (3) cover. Responsibilities held by learners in a globalized world is good. The development of learner responsibility are integrated into the learning Civics are very significant change. The solution was developed in an effort to character development responsibilities of learners focused on the development of media, methods and more innovative learning model. Supporting factor is the advancement of all fields of technology, for example, information, and communication can be utilized in the learning process.